Expert auto-tuner for multivariable control applications - Toh, Kar Ann. (2009)
An expert auto-tuner for multivariable control applications is proposed. The main idea of the auto-tuning control methodology is to apply SISO (Single-Input-Single-Output) PID (Proportional, Integral and Derivative) controller with appropriate adaptation for the MIMO (Multi-Input-Multi-Output) environment. The reasons for choosing the PID controller include its robustness and its well balanced action to reduce offset and to improve response. More importantly, the PID controller has been widely accepted in the industry with its clear physical meaning of the controller parameters. An expert tuning processor is designed to operate on the PID controller to provide good tuning parameters based on the observed response.